Aplikasi Pestisida Nabati Umbi Gadung (Dioscorea hispida) untuk Mengendalikan Hama Ulat Grayak (Spodoptera frugiperda) pada Tanaman Jagung (Zea mays) di Laboratorium Pengamatan Hama dan Penyakit Tanaman (LPHP) Banyumas - Eka Wihartati; Arif Prashadi Santosa; Ardiana Kartika B (UM Purwokerto Press, 2021)
One of the pests that attack corn plants in Banyumas is the armyworm pest (Spodoptera frugiperda) which has been endemic since early 2019. This pest can cause damage to up to 70% of the total land area of the corn crop. Generally, pest control is carried out using chemical pesticides which have a negative impact on the environment and health. Therefore, to overcome these negative impacts it is necessary to do better control such as control using vegetable pesticides or biopesticides. One of the plants that can be used as vegetable pesticides is the gadung tuber which contains diosgenin, steroid, saponin, alcohol, and phenol compounds. This study aims to determine the difference in the effectiveness of the vegetable pesticides of the gadung tubers which were extracted using two different methods, namely by blending and boiling. The resulting vegetable pesticides were applied to 25 samples of the pest Spodoptera frugiperda. The method of analysis used a qualitative descriptive method. The results showed that after the application of vegetable pesticides twice the samples of the caterpillars used were dead, which was indicated by the visual death appearance of Spodoptera frugiperda where the body turned stiff and secreted fluid, the color of the body turned blackish brown (burnt). The difference in the effectiveness of the results of the application of vegetable pesticides was seen in the mortality rate of caterpillars where for the caterpillars that were applied with boiling of 25 samples, 12 caterpillars that died on the second day, the third day 5, the fourth day 4 caterpillars and the fifth day 4 caterpillars. Meanwhile, for the death rate of caterpillars that were applied with blending of 25 samples, the caterpillars that died on the second day were 10, the third day 7, the fourth day 6, and the fifth day as many as 2 caterpillars. The application of both gadung tuber vegetable pesticides made by blending and boiling is considered equally effective in controlling armyworm pests but seen from the faster mortality rate using vegetable pesticides made by blending.